The Weak Byzantine Generals Problem - Lamport, Leslie (Journal of the Association for Computing Machinery, 1983)
This paper introduces a weaker version of the Byzantine generals problem described in [41]. The problem is "easier" because there exist approximate solutions with fewer than 3n processes that can tolerate n faults, something shown in [41] to be impossible for the original Byzantine generals problem. I don't remember how I came to consider this problem.